Encyclopaedia Britannica 2004 ultimate reference suite. (Encyclopaedia Britannica, 2004)
Contains Encyclopaedia Britannica, Britannica Student Encyclopedia, and Britannica Elementary Encyclopedia, 101,000 articles, 300,000 dictionary entries, 500,000 thesaurus entries, a world atlas, 2,775 maps and 25,000 images and multimedia.